Analysis of Radical and Radicalism Collocations in Indonesia Online Media Reporting Based on Linguistics Corpus - Pirmansyah Pirmansyah; Fahmy Lukman (KEDJATI Journal of Islamic Civilization, 2024)
In 2018, the words Radical and Radicalism (RaR) became very popular and a matter of public discussion. Reporting on this issue was directed at radical movements and acts of terrorism that had entered the academic environment on campus. This research analyzed the meaning of collocation of RaR in online media reporting. This study used a combined approach: quantitative and qualitative. Quantitative was used to gather data from the linguistic corpus (digital linguistics) taken from online news media such as Detik.com, Okezone.com, Kompas.com, Viva.co.id, Media Indonesia, Kompas, Bisnis Indonesia, Pikiran Rakyat, Republika Online, BBC.com, and CNN Indonesia.com. Qualitative was used to identify the number of frequencies of the word Radical and the occurrence of the collocation of RaR, as well as clusters/n-grams contained in the AntConc application tools. The results show that the words RaR were powerful for Islamic groups, with the high frequency of appearance of the word radicalism in rank 7 with a frequency of 624, Islam in rank 16 with a frequency of 355, religion in rank 24 with a frequency of 249, and campus in rank 32 with a frequency of 200. Hence, this data reveals that online media tended to be subjective in reporting, where radical groups always connoted certain religious groups and symbols. Moreover, the radical movement was suspected to have spread this term among students on several campuses in Indonesia, especially Islamic groups. Thus, this research provides an overview of the RaR collocation on online news.